DIDACTIC GAMES IN TEACHING ENGLISH LESSONS - NORMATOVA MUKADDAS BAXODIROVNA (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
Achieving fluency in English requires a consistent and immersive approach to language learning. While there are no shortcuts, specific strategies can significantly expedite the journey to fluency. This article outlines effective methods for learners, including immersion in the language, regular speaking practice, thinking in English, and engaging with interactive tools and using didactic games. By focusing on vocabulary acquisition, extensive reading and writing, and setting structured goals, learners can enhance their language skills more quickly. Ultimately, the key to fluency lies in daily practice, motivation, and a proactive approach to learning.